Women's Experimental Cinema Critical Frameworks - Blaetz, Robin (Duke University Press, 2007)
Women's Experimental Cinema provides lively introductions to the work of fifteen avant-garde women filmmakers, some of whom worked as early as the 1950s and many of whom are still working today. In each essay in this collection, a leading film scholar considers a single filmmaker, supplying biographical information, analyzing various influences on her work, examining the development of her corpus, and interpreting a significant number of individual films. The essays rescue the work of critically neglected but influential women filmmakers for teaching, further study, and, hopefully, restoration and preservation. Just as importantly, they enrich the understanding of feminism in cinema and expand the terrain of film history, particularly the history of the American avant-garde.